Formulation and optimization control of a class of networked evolutionary games with switched topologies. (November 2016) - Zhao, Guodong; Wang, Yuzhen
Abstract: This paper studies the algebraic formulation and optimization control for a class of networked evolutionary games with switched topologies via the semi-tensor product method. First, an algebraic expression is formulated for the given networked evolutionary games, based on which, the behavior of corresponding evolutionary games is analyzed. Then, under some certain assumptions, the existence of fixed points for the given systems is proved and a free-type control sequence is designed to guarantee the best strategy profile reachable globally. Finally, an illustrative example is studied to support our new results.